{The Emerging Role on the Use of Platelet-Rich Plasma Products in the Management of Urogynaecological Disorders.} - Prodromidou, Anastasia; Zacharakis, Dimitrios; Athanasiou, Stavros; Protopapas, Athanasios; Michala, Lina; Kathopoulis, Nikolaos; Grigoriadis, Themos (Surgical innovation, 2022)
Background: The regenerative efficacy of platelet-derived products has been recently investigated in the treatment of pelvic floor disorders (PFDs). We aimed to synthesize the current evidence of platelet-rich plasma (PRP) products used in urogynaecological disorders including vaginal atrophy, pelvic organ prolapse (POP), urinary incontinence, vaginal fistulas and vaginal mesh exposure. Methods: A meticulous search of the currently available literature on the use of PRP for the management of PFDs was performed using 3 electronic databases. Results: PRP could be a feasible alternative modality for the management of vaginal atrophy with favourable outcomes in vaginal atrophy parameters and patients' satisfaction, especially when hormone therapy is contraindicated. In patients with POP, an increase in collagen concentration after PRP application was observed while the use of PRP resulted in improvement of stress urinary incontinence symptoms. A considerable proportion of vesicovaginal fistulas were treated after application of PRP-based injections. Conclusions: There is only limited evidence of the use of PRP for PFDs. Platelet-rich plasma appears to be a promising, easy to apply, cost-effective and feasible alternative therapeutic modality for the management of various urogynaecological disorders. Future randomized trials are needed to confirm the efficacy of PRP in the treatment of urogynaecological disorders.
Keywords: Collagen; Female; Humans; Pelvic Organ Prolapse; Platelet-Rich Plasma; stress; therapy; Urinary Incontinence; Vagina